Life Cycle Assessment on Cement Treated Recycling Base (CTRB) Construction - Sudarno Sudarno; Purwanto Purwanto; Pratikso Pratikso (Waste Technology, 2014)
LCA is one of the few environmental management techniques that are used to perform a risk assessment, environmental performance evaluation, environmental auditing, and environmental impact assessment and must be applied to the construction CTRB. The purpose of this study was to determine the amount of energy consumption is used and determine the amount of emissions (CO2) in the implementation of the Foundation Layer Top (base course) with the former asphalt pavement aggregate blended cement / Recycling Cement Treated Base (CTRB). This study uses: (i) Compilation and data inventory of relevant inputs and outputs of a product system; (ii) Evaluating the potential environmental impacts associated with the data input and output; (iii) Interpret the results of the inventory analysis and impact assessment in relation to the research objectives. The results showed that Energy consumption in the implementation of recycling pavement (CTRB) is 225.46 MJ / km of roads and the resulting GHG emissions 17,43Ton CO2 / km of roads. Previous researchers to calculate the energy consumption of road works on the implementation of conventional (hotmix) is 383.46 MJ / km of roads and the resulting GHG emissions 28.24 Ton CO2 / km of roads. If the calculated difference between a job and Hotmix CTRB and then a comparison is made CTRB energy consumption is 158 MJ / km of road, this happens 70.07% savings and GHG emissions resulting difference is 10.81 tons of CO2 / km of road, resulting in a decrease in 62,02%.